Hubungan Pola Makan dengan Kejadian Dispepsia pada Remaja Putri di Pesantren Hidayatullah Tanjung Morawa pada Tahun 2023 - Naela Alfin Ni’mah; Faisal Balatif; Marzuki Samion; Anna Yusria (Pusat riset dan Inovasi Nasional, 2025)
Based on WHO data, cases of dyspepsia in the world reach 13-40% of the total population each year. Dyspepsia is one type of non-communicable disease that occurs not only in Indonesia, but also in the world. Irregular eating patterns, consumption of certain types of food such as sour, spicy and irritating foods are some of the factors that cause dyspepsia. To determine the relationship between dietary patterns and dyspepsia in female adolescents at the Hidayatullah Tanjung Morawa Islamic Boarding School in 2023. This study uses an analytical observational method with a cross-sectional approach, data collection using questionnaires and interviews. Data analysis using univariate tests and bivariate tests using the chi-square test. The majority of respondents were aged <16 years (70.3%). The incidence of dyspepsia was 70.3% or 45 respondents, of which 25 people (39.1%) had poor diet. Of the 29.7% of respondents who did not experience dyspepsia, 13 people (20.3%) had good diet. The majority of respondents often consumed spicy foods (67.1%) but rarely consumed sour foods (56.2%) and irritative foods (65.6%). The bivariate results between the relationship between diet and dyspepsia, spicy foods and dyspepsia, sour foods and dyspepsia, and irritative foods and dyspepsia were p-values ​​of 0.037, 0.041, 0.013, 0.526, respectively. There is a relationship between dietary patterns, types of sour and spicy foods with the incidence of dyspepsia, but there is no statistically significant relationship between the types of irritating foods and the incidence of dyspepsia in female adolescents at the Hidayatullah Tanjung Morawa Islamic Boarding School.